2022
DOI: 10.33594/000000578
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle and Kidney Crosstalk in Chronic Kidney Disease

Abstract: The functioning of complex organisms requires a constant and delicate balance of processes both between and within cells, tissues, and organ systems. There is growing appreciation for the role of signalling crosstalk connecting different organ systems of the body, even from tissues traditionally classified as "inert" in terms of their capacity to produce chemical signals that can act on other organ systems. Many of these secreted molecules have been shown to contribute to, or exacerbate, a variety of functions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 91 publications
0
2
0
Order By: Relevance
“… 48 Therefore, inhibition of muscle atrophy may prevent CKD progression. 53 Studies have shown that the genetic knockout of MG53 in mice results in muscle dystrophy, along with decreased kidney function. 10 , 17 , 23 Moreover, rhMG53 was demonstrated to relieve muscle fibrosis and affect histological structures in a mouse model of muscular dystrophy.…”
Section: Mg53 and Kidney Fibrosismentioning
confidence: 99%
“… 48 Therefore, inhibition of muscle atrophy may prevent CKD progression. 53 Studies have shown that the genetic knockout of MG53 in mice results in muscle dystrophy, along with decreased kidney function. 10 , 17 , 23 Moreover, rhMG53 was demonstrated to relieve muscle fibrosis and affect histological structures in a mouse model of muscular dystrophy.…”
Section: Mg53 and Kidney Fibrosismentioning
confidence: 99%
“…Although kidney-related mechanisms involved in maintenance of musculoskeletal health [14,[17][18][19][20][21] have been intensively researched for decades and the association between CKD and osteoporotic fractures (OF) is well established [22,23], studies on CKD combined with HF, the most devastating complication of osteoporosis (OP), are relatively rare [13,24,25]. Te relationship between kidney function and postoperative outcomes in hip fracture (HF) patients has not been systematically investigated, and the few studies that evaluated the input of CKD on HF outcomes have yielded conficting results [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%